Restoration of F' superinfection inhibition in a DnaB mutant of Escherichia coli upon construction of heterozygous DnaB merodiploids or P1 lysogens carrying a dnaB analogue. - Bezanson, G S (1975)
F-prime derivatives of the Escherichia coli strain CR34 bearing the thermosensitivity mutation dnaB43 display low levels of plasmid-determined superinfection inhibition in conjugational crosses at 30 C. Salt-mediated phenotypic suppression of this temperature sensitivity fails to restore normal levels of inhibition, indicating its alteration is not a secondary effect of dnaB43 a-tion on growth or deoxyribonucleic acid syntheiss. Superinfection inhibition is fully restored in mutant cells made merodiploid for the dnaB region by introduction of the F' dnaB-+ plasmid F134-1. dnaB43-bearing strains lysogenized with P1 phage contribution dnaB-analogue protein show eight to nine times more superinfection inhibition than do the same cells carrying P1 prophage repressed dnaB-analogue protein production. Taken together, this evidence suggests a direct causal relationship between dnaB43 and the altered superinfection inhibition phenotype.